Out loud: The experience of literature in the digital space. Issue 2 (1st December 2020) - Warner, Marina
In the present climate of discouragement that threatens all of us who hold the Humanities dear, one of the worst threats, or so it seems, has been the dumbing down consequent on digital media and the rise of hate speech on digital platforms. I want to offer some countervailing reflections and hopes, and explore the activity and the potential of the World Wide Web as a forum for literature; in spite of the instinctive recoil and bristling horror I feel for social media as currently used, it is possible to consider and reframe the question of reading on the web. Doing so leads to the questions, what is literature and can literature be found beyond the printed book? It is my contention ‐ perhaps my Candide-like hope ‐ that the internet is spurring writers on to creating things with words that are not primarily aimed at silent readers but at an audience that is listening and viewing and feeling, and maybe also reading all at the same time, participating in word events channelled through electronic media.